Preferences of fruit-feeding butterfly on bait trap in Soraya Research Station, Leuser Ecosystem, Aceh, Indonesia - ITSNATANI SALMA; ZURIANA SIREGAR; ALIA RIZKI; SUWARNO SUWARNO (Jurnal Natural, 2021)
Butterflies are insects that live cosmopolitan. Some butterflies in tropical forests look for food sources from sucking the juice of ripe fruits that have fallen on the forest floor. Fruit-feeding butterflies can adapt in finding food sources, selecting and sucking food effectively. Fruit contains varying concentrations of sugar and nitrogen. The existence of fruit-feeding butterflies in tropical rain forests is influenced by the availability and quality of food sources as well as other supporting factors such as temperature, humidity, and light intensity. The purpose of this study was to identify fruit-feeding butterflies and their preferences for banana and pineapple baits in the Soraya Research Station Area, Leuser Ecosystem, Aceh, Indonesia from September to November 2020. Six forest trail locations were selected as trap locations. A total of 360 cylindrical gauze baited traps (80 cm high and 35 cm diameter) were installed on six trails/line transects. Baited traps were set at three different heights, that is at the understorey level (± 0-2 m), midstorey level (± 5-6 m), and overstorey level (± 10-11 m) with a distance of ± 5-10 m. The distance between location points is ± 250 m. The fruit baits used in this trap were ripe bananas and pineapples. The results obtained were 37 species with 176 individuals trapped on banana bait and 50 species with 183 individuals on pineapple bait. However, the results of the t-test using the Man-Whitney test showed no significant difference between the banana and pineapple bait used.